Sleep Duration and Pain Intensity in Medical Students with Tension-Type Headache: A Cross-Sectional Study - Annisa Permata Eqlevina; Tasya Meidy Pradhana; Yusak Mangara Tua Siahaan (Lumina : Indonesian Journal of Neurology, 2026)
Introduction: Tension-type headache (TTH) is the most common primary headache disorder and frequently affects medical students. Sleep disturbances, particularly insufficient sleep duration, have been implicated as risk factors that may worsen headache intensity. This study aimed to investigate the relationship between sleep duration and pain intensity among medical students with TTH at Universitas Pelita Harapan. Methods: A cross-sectional analytic study was conducted from February to May 2025. A total of 186 students were screened, and 84 met the inclusion criteria. TTH was assessed using a validated 13-item questionnaire, pain intensity was measured with the Numeric Rating Scale (NRS), and sleep duration was self-reported and categorized as sufficient (≥7 hours) or insufficient (<7 hours). Stress levels were controlled using the 10-item Perceived Stress Scale (PSS-10). Data were analyzed with the Pearson Chi-Square test, and odds ratios (OR) with 95% confidence intervals (CI) were calculated. Results: Most participants were female (70.2%), and the majority reported insufficient sleep (65.5%). Moderate and severe TTH pain was reported by 39.3% and 39.3% of respondents, respectively. A significant association was observed between insufficient sleep and higher pain severity (p < 0.001). Students with insufficient sleep were 32.6 times more likely to report moderate–severe pain compared to those with sufficient sleep (OR = 32.615, 95% CI: 6.650–159.973). Conclusion: Short sleep duration is strongly associated with increased pain intensity in medical students with TTH. Keywords: Tension-Type Headache, Sleep Duration, Pain Intensity, Medical Students, Numeric Rating Scale